1997
DOI: 10.1557/proc-486-213
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Optical Properties of Si Nanocrystals In SiO2: Materials Issues And Nanocrystal Laser Perspectives

Abstract: Si nanocrystals (diameter 2 – 5 nm) were formed by 35 keV Si+ implantation at a fluence of 6×1016 Si/cm2 into a 100 nm thick thermally grown SiO2 film on Si (100), followed by thermal annealing at 1100 °C for 10 min. The nanocrystals show a broad photoluminescence spectrum, peaking at 880 nm, attributed to the recombination of quantum confined excitons. Rutherford backscattering spectrometry and transmission electron microscopy show that annealing these samples in flowing O2 at 1000 °C for times up to 30 min. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…[1][2][3][4] Forming Si nanocrystals by means of Si ion implantation into SiO 2 followed by precipitation has been extensively studied [5][6][7][8][9][10] and SiO 2 has proven to be a robust matrix that provides good chemical and electrical passivation of the nanocrystals. Previously, we have demonstrated that SiO 2 films containing Si nanocrystals made by ion implantation show photoluminescence in the visible and near-infrared that can be attributed to two distinct sources.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Forming Si nanocrystals by means of Si ion implantation into SiO 2 followed by precipitation has been extensively studied [5][6][7][8][9][10] and SiO 2 has proven to be a robust matrix that provides good chemical and electrical passivation of the nanocrystals. Previously, we have demonstrated that SiO 2 films containing Si nanocrystals made by ion implantation show photoluminescence in the visible and near-infrared that can be attributed to two distinct sources.…”
Section: Introductionmentioning
confidence: 99%
“…11) Such materials exhibit strong photo-and electroluminescence (PL and EL) in visible and near-infrared wavelengths, which attracts much attention due to the potential applications in electronic and optoelectronic devices. [12][13][14][15] Most of the studies on these materials discuss light-emitting properties of the metal-oxide-semiconductor (MOS) structure with Si nanocrystals buried in the surface oxide layer on the silicon substrate. The combined carrier transport effects of the conventional MOS diode, the implanted Si-related defects, and the buried Si nanocrystals in the SiO 2 layer on Si substrate are thus complicated.…”
mentioning
confidence: 99%